ANALISIS SUPPLY CHAIN MAPPING KOMODITI KOPI ROBUSTA DI PROVINSI LAMPUNG - Fitri, Melani Anisa; Akbar Serawai, Bembi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Coffee production in Indonesia, although showing consistent growth, has not been accompanied by an increase in farmers' income, which is largely due to inefficiencies in the marketing system and supply chain. This study aims to identify the actors and their roles in the Robusta coffee supply chain system in Lampung Province and to analyze the structural mapping of the Robusta coffee supply chain network in Lampung Province. The method used is a descriptive survey with an explanatory approach, supported by in-depth interviews, field observations, and informal discussions. Respondents were selected purposively and through snowball sampling techniques, including coffee farmers, agro-industry actors, export companies, government agencies, and multinational companies, with a total of 12 respondents. The results of the study show that the robusta coffee supply chain system in Lampung consists of six main channels involving actors from upstream to downstream, with diverse interaction and partnership patterns. Product flows include coffee in the form of beans and powder; information flows encompass the exchange of technical data and quality standards; and financial flows are facilitated through various payment schemes, incentives, and partnership contracts. It is necessary to strengthen partnerships and increase farmer capacity to improve system efficiency and the welfare of upstream actors in the long term.